Think global—act local: the challenge of producing actionable knowledge on transboundary climate risks at the sub-national level of governance - Aall, Carlo; Holm, Tara Botnen; Cauchy, Adeline; Rudolf, Florence; Harris, Katy; Jansen, Marta K.; Gobert, Julie; Lager, Frida; Arvis, Blandine; Bour, Muriel (Frontiers in Climate, 2023)
A growing number of countries are putting transboundary climate risks on their national adaptation policy agenda. The designation of subnational governments as key actors in climate change adaptation policy appears to be appropriate when the risks associated with climate change are defined as 'local'. In this study we have investigated whether local authorities can plausibly play an equally central role when it comes to transboundary climate risks. Three cases have been studied: Paris in France and the topic of migration and integration, Klepp in Norway and the topic of agriculture and livestock production, and the river harbours in the Upper Rhine region of France and the topic of freight transportation and river regulation. Even if the sub-national actors involved in the three cases showed strong interest in analysing and addressing transboundary climate risks, it remains an open question whether such authorities can and should play an equally central role in addressing transboundary climate risks as they do in the case of local climate risks. On the other hand, assigning responsibility for managing transboundary climate risks exclusively to national authorities may increase the risk of conflicts between measures to reduce local climate risks (frequently developed and implemented by sub-national authorities) and transboundary climate risks. The authors of this paper therefore advocate a strong partnership between the different levels of governance, and between public and private-sector stakeholders, in adaptation to transboundary climate risk. It is therefore crucial that national governments explicitly account for transboundary climate risks in their national adaptation agendas and, as part of their process in determining 'ownership' of such risks, decide on the role sub-national authorities should play. This choice will also affect the role of local authorities in managing local climate risks due to the interlinkages between them.